Is Duration of Endotracheal Tube Intubation Using a Video Laryngoscope Different with a Direct Laryngoscope in Elective Surgery Patients During Pandemic Covid-19? - Zaky Hasan; Zulkifli; Agustina Br Haloho; Irfannuddin (Journal of Anesthesiology and Clinical Research, 2021)
Introduction: Aerosol box is a usefull tools to prevent aerosol and droplet contaminations during laryngoscopy and intubation in COVID-19 pandemic. Video laryngoscope is recommended during this era to increase the operator and patient’s distance during the procedure. However, many anesthesiologists still use direct laryngoscopes due to their availability and familiarity. This study aims to compare endotracheal tube intubation with video laryngoscope compared to direct laryngoscope in elective surgery patients. Methods: This study was a quasi-experimental study. The sample size in each group (video and direct laryngoscope) was 35 subjects. The primary outcome of this study was to compare the duration of intubation between video laryngoscope and direct laryngoscope, while the secondary outcome was to evaluate complications such as broken teeth and sore throat 24 hours post intubation. Results: Direct laryngoscope had shorter intubation duration than video laryngoscope [12.3 (8.9-21.0) vs 13.3 (11.4 – 21.6; p =0.07) respectively. Two complication reported on video laryngoscope groups. Conclusion: Duration of ETT intubation using a direct laryngoscope was shorter during intubation with aerosol box compared to video laryngoscope in elective surgery patients. The box which was being used may limit the space of movement making it difficult to intubate.